ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Yulia Pratiwi Siregar; Rabiyatul Adawiyah Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Education aims to create quality human resources and be able to carry out the goals of education and one of them is the ability to solve mathematical problems. This type of research is descriptive research by carrying out a literature review of 10 journals. Based on the review conducted, it was concluded that abilities are very important for every student, teacher, and facilitator to have. Problem solving abilities can also collaborate with self-confidence, self-creativity, and innovation in improving academic achievement and enhancing future careers.